PENGARUH PEMBINAAN DAN DISIPLIN GURU OLAHRAGA TERHADAP PENGEMBANGAN EKSTRAKURIKULER BOLA VOLI - Hadi Kosasih, Alam (STKIP Subang, 2017)
The research entitled The Influence of Coaching And Discipline of Teacher Exercise on Vitar Ball Extracurricular Development is aimed to find out whether there is an influence between